Power, the state, and sovereignty : essays on international relations - Krasner, Stephen D., 1942- (Routledge, 2009)
Stephen Krasner has been one of the most influential theorists within international relations and international political economy over the past few decades.€ This book is a collection of his key academic work as well as a meditation on his time in office.